Power System Monitoring with IoT Approach - Anuar, Muhammad Abdullah; Utomo, Wahyu Mulyo (Evolution in Electrical and Electronic Engineering, 2022)
Internet of Things is an advance technology and works very efficiently. By featuring with the sense devices which provide the measurement and calculation for the monitoring purpose, it’s become powerful to able control and monitor for electrical practitioner in order made a decision or evaluation. In this project, the objective of power system monitoring to develop a device with current and voltage sensor for measuring the voltage and current signal and compute the data that can easily access using internet of things platform. After that, the performance evaluation taking place for the devices with measurement tools to verify the data. Next, the component of the project is ESP32 development board that work for computing on value of the real power, apparent power, power factor, Root mean square of voltage and current. The input of the ESP32 development board is the voltage sensor and current sensor which sensing the voltage and current waveform for instantaneous waveform. From that, the error of the between measurement satisfying which had been below the 10% from the actual value from the measurement.